Kenyamanan Termal Rumah Tinggal Vernakular Di Wilayah Lereng Gunung; Studi Kasus Dusun Kabelukan, Desa Candi Yasan, Kecamatan Kertek, Kabupaten Wonosobo, Jawa Tengah - Supriyono Supriyono; VG. Sri Rejeki; A. Ardiyanto; Hapsari Hapsari (Tesa Arsitektur, 2018)
Indonesia has a humid tropical climate with many different topographies, which is makes it has a very striking temperature difference. Wonosobo is one of the regencies in Central Java which is located in a mountainous region with the air temperatures is between 14.3 - 26.5 degrees C. Kertek is one of the districts in the Wonosobo regencies which is located at an altitude of 700 m - 1,150 m above sea level, with the temperature during the day ranged from 26 deg.C - 29 deg.C and at the night 20 deg. C - 22 deg. C. Kabelukan is a village in the Kertek district area which is located on a mountain slope with hilly topography. The settlement environment is the result of vernacular architectural products with the uses of natural ventilation.Thermal comfort is a condition in which a human feels comfort in their environment which is achieved by conditions of air temperature, humidity, wind movement, use of clothing and activities. This factor will be examined by qualitative rationalist methods supported by quantitative data. Primary data is taken from temperature, humidity and wind measurements, analyzing the floor plans and also have an interview with the residents supported by secondary data.The result is for looking a ventilation system that has not been fully utilized that makes the humidity level is high and above of comfort zone level. This is happened because peoples who live there (residents) have adapted to their environment and get used to live with these environmental conditions. So they need to be directed and advised when they want to make or repair their house to paying attention on the ventilation placement in order to obtain the maximum level of thermal comfort.